Teen pregnancy in a Hospital in Paraguay in 2011 - Cabañas Acosta, Beatriz Mercedes (2016)
Objective: To describe the epidemiological characteristics of teenage pregnancy in the Regional Hospital of Coronel Oviedo, Paraguay. Material and Methods: Descriptive, observational cross-sectional study with consecutive non-probability sampling of cases, review of medical records of pregnant teenagers who attended the Regional Hospital of Coronel Oviedo, Paraguay between january and december 2011. Results: 167 medical records of pregnant adolescents were included, which accounted for 40.7% of all births attended in 2011. The age range was between 13 and 19 years, with an average age of 17.47 ± 1.42. 64.1% were of urban origin. 86.8% did not use contraception and 50.9% had a free union. The observed complications were: premature rupture of membrane at 10.2%, urinary tract infection at 8.4% and fetal death in 0.6% of cases. Conclusion: The prevalence of teenage pregnancy in this study was 40.7%; most women did not use any contraceptive method. The most common complication in this type of pregnancy was premature rupture of membrane.